The use of logistic regression method in data classification with practical application of Covid-19 patients in Nasiriya General Hospital - IRAQMOON; Hussein Enad, Fahad (University of Thi-Qar Journal, 2022)
This research deals with the study of binary logistic regression method for classifying data for Covid-19 patients, Covid disease is one of the largest health problem that swept the world at the present time, causing many economic problems in the world, as the research aims to know the correct classification of the influencing factors and to demonstrate the accuracy of the method in the classification, as data for Covid-19 patients were used in the Nasiriya General Hospital in Dhi Qar, several criteria were relied on, the most important of which is the correct classification ratio of the observations to indicate the performance and efficiency of the method used. The Maximum Likelihood Estimation and Weighted Least Squares methods were also used to estimate the parameters, the obtained results showed that the logistic regression method performed well in the accuracy of the correct classification of observation.